Give me your hand [large type] - Abbott, Megan., 1971- (Thorndike Press large print basic, 2018)
Kit Owens harbored only modest ambitions for herself when the mysterious Diane Fleming appeared in her high school chemistry class. But Diane's academic brilliance lit a fire in Kit, and the two developed an unlikely friendship-- until Diane shared a secret that changed everything between them. More than a decade later, Kit has begun to fulfill the scientific dreams Diane awakened in her. But the past comes roaring back when she discovers that Diane is her competition for a position both women covet: taking part in groundbreaking new research led by their idol.